Reaching out to our community / Associate Professor Dr Angeline Ranjethamoney Vijayarajoo, Afni Anida Adnan and Sharina Salmi Azmi - Vijayarajoo, Angeline Ranjethamoney; Adnan, Afni Anida; Azmi, Sharina Salmi (Universiti Teknologi MARA, Negeri Sembilan, 2023)
On September 3rd, 2023, we were alerted to a situation where a lady (Lala, a pseudonym is used to protect her privacy) in the community was ill at home and who also fell within the B40 group. Basically, she needed help. What was most important was medical aid. Only a doctor could help. This is when we decided to collaborate with Dr R. Elangovan Radakrishnan, our Panel doctor at Policlinic Seremban 3, one of our UiTM Panel clinics.